IMPLEMENTING A QUALITY LEARNING IN SCHOOLS - Warisno, Andi (UIN Ar-Raniry, 2018)
A quality learning process is a process of learning based on continuous improvement. The quality can be measured from the quality of inputs, processes, and outputs. In its implementation, it requires a culture of quality that grows from all parties: teachers, school principals, students, staff, cleaning service, and all of the school’s components. By improving the quality of learning, it means we have improved the quality of education as a whole.